Drone-based photos, 3D models, DSM and orthomosaics and ground-based catalogues of lava fountain times, shape, and amplitude during the Geldingadalir 2021 eruption, Iceland - Eibl, Eva P. S.; Heimann, Sebastian; Joachim, Alea; Gnauck, Undine; Hamzaliyev, Shaig; Moreland, William M.; Helgason, Sigurður þór (GFZ Data Services, 2024)
Abstract The Geldingadalir 2021 eruption in Iceland started on 19 March and ended on 18 September. It featured nearly 9000 lava fountain episodes of minute to day duration that were all accompanied by seismic tremor. We measured the duration, repose time, tremor amplitude and shape using seismometers from the University of Potsdam. We publish the corresponding catalogs that contain information about these episodes. Periodically, aerial surveys were conducted by the University of Iceland using unoccupied aerial systems (UAS). These surveys lead to digital surface models (DSM), orthomosaics, and 3D models. These products were used to supplement the seismic observations.